Nonlinear relationship between early postnatal weight gain velocity and neurodevelopmental outcomes in very-low birth weight preterm infants: A secondary analysis based on a published prospective cohort study - Luo, Zhongchen; You, Beibei; Zhang, You; Tang, Jiao; Zheng, Zehong; Jia, Yuling; Wang, Li; Zeng, Dan; Li, Hong; Wang, Xiuhong (Frontiers in Pediatrics, 2022)
Abstract Background: Extrauterine growth restriction among the very-low birth weight preterm infants (VLBWPIs) is associated with poorer cognitive development outcome, while the rapid weight gain in infancy increases the long-term risk of obesity and non-communicable disease among VLBWPIs. However, the results of research on the association between early postnatal growth velocity and neurodevelopmental outcomes in VLBWPIs are still limited and controversial. Objective: We aimed to explore the association between the growth velocity in early postnatal and neurodevelopmental impairment among VLBWPIs. Methods: This study was a secondary analysis of a previously published prospective cohort. It was based on data on 1791 premature infants with a birth weight of less than 1500 g, registered in the database of the Premature Baby Foundation of Taiwan between 2007 and 2011. A binary logistic regression model was used to evaluate the association between the weight gain velocity in different periods (from birth to 6 months corrected age (CA), 6 to 12 months CA and 12 to 24 months CA) and neurodevelopmental impairment (NDI), respectively. The generalized additive model and the smooth curve fitting (penalized spline method) were used to address nonlinearity, and a two-piece wise binary logistic regression model was added to explain the nonlinearity further. Results: Nonlinearities were observed between NDI and the weight gain velocity from birth to 6 months CA (Inflection point 20.36, < Inflection point: OR=0.75, 95% CI 0.67, 0.84, > Inflection point: OR=1.01, 95% CI 0.97, 1.05), 6 to 12 months CA (Inflection point 9.44, < Inflection point: OR=0.89, 95% CI 0.84, 0.94, > Inflection point: OR=1.05, 95% CI 1.05 (1.00, 1.11), and 12 to 24 months CA (Inflection point 16.00, < Inflection point: OR=0.93, 95% CI 0.88, 0.98, > Inflection point: OR=1.75, 95% CI 1.05 (0.96, 3.08). Conclusion: The neurodevelopmental benefits from a rapid weight gain velocity from birth to 24 months CA might be limited once the growth pace reaches an optimum level. It would help find a pattern of growth that facilitates optimal neurodevelopment, yet minimizes negative health consequences as sociated with overnutrition further.